Targeted Delivery of Nanopesticides and Nanofertilizers in Sustainable Agricultural Farming - Nazeer, Ayesha; Ahmad, Faisal; Verma, Neeraj; Ahmad, Shamim (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
Nanofertilizers and nanopesticides increase crop efficiency because of a several-fold increase in the surface-to-volume ratio of nano-forms of nutrients and their suitability to foliar application. The potential agricultural benefits of these nanomaterials, their modes of action, and the fate of nanomaterials in the soil are all discussed. This book uses a multidisciplinary approach and highlights the expertise of the authors in the fields of materials science, nanotechnology, nanobiosensors, and agricultural research. It describes the details of nanoscale synthesis of materials for targeted delivery; in vitro, in vivo, and field trials experimentation; how to use digital technology for specific solutions including Big Data to create predictive mathematical modelling; along with the core knowledge of plant systems and their biosphere to improve crop yields. Also, the book discusses future perspectives and challenges of nanomaterials in agricultural applications. In summary, this book discusses agricultural nanobiotechnology with its main emphasis on understanding the interactions of nanoscale materials of pesticides and fertilizers. It also covers their application to improve the quality and increase crop yield with a minimum use of the active ingredients attached to the nanocarriers.
Preface -- Foreword -- Acknowledgment -- 1. Nanoscience, Nanotechnology and Engineered Nanomaterials - An Introduction -- 2.Nanomaterials and Plant Biomolecules - Basics of Interactions -- 3.Nanomaterials and Phytonanobiotechnology -- 4. CNMs and CDs in Plant Growth 5.Nanofertilizers in Agriculture -- 6.Pesticides and Crop Protection -- 7.Nanotechnology and Crop Management -- 8. Targeted Delivery of Nanopesticides -- 9. Nanopesticides in Agriculture: Some Examples -- 10. Revelance of Nanopesticides and Nanofertilizers in Sustainable Agriculture -- 11. Nano-enabled Agrotechnology: Current Status -- 12. Nano-agro-biotechnology Prospects -- 13. Future Aspects -- Index.
Keywords: Plant biotechnology; Nanobiotechnology; Plant molecular biology; Agricultural biotechnology; Agricultural genome mapping; Plant Biotechnology; Nanobiotechnology; Plant Molecular Biology; Agricultural Biotechnology; Agricultural Genetics